Determinação voltamétrica do terapêutico redox-ativo Mn(III) N-metilpiridilporfirina em matriz biológica - Mascarenhas, Ana Carolina Vieira (2017)
Cationic Mn porphyrins (MnPs) derived from 2-N-pirydilporphyrins are among the most potent superoxide dismutase (SOD) mimics and catalytic redox modulators of oxidative stress for pre-clinical studies and are currently under phases I/II Clinical Trials in Canada and USA as redox-active therapeutics. The activity of MnPs in vivo depends not only on their intrinsic catalytic potency, but also on other factors, such as cell accumulation and bioavailability. The quantification of MnPs in biological milieu demands reliable and sensitive analytical techniques. In the present work a voltammetric method for quantification of the prototypical MnP, meso-tetrakis(N-methylpyridinium-2-yl)porphyrin (MnTM-2-PyP5+) was developed using yeast Saccharomyces cerevisiae biomass as a model for biological samples. The voltammetric measurements were carried out using Ag/AgCl electrode and platinum electrode as reference and auxiliary electrodes, respectively, in 0.05 mol L-1 phosphate buffer (pH 7.8) containing 0.1 mol L-1 NaCl. For the development of the method, differential pulse voltammetry (DPV) and square wave voltammetry (SWV) techniques were evaluated, with SWV being the most sensitive to the analyte. As working electrode, four types of carbonbased electrodes were evaluated: glassy carbon electrode (GCE), carbon paste electrode (CPE), carbon nanotube paste electrode (CNTE), and carbon nanotube and carbon paste electrode (CNTCPE). The CNTCPE was the most sensitive whereas GCE was the most selective. Therefore, CNTCPE and GCE were used as working electrodes for method development. SWV parameters were optimized and the obtained analytical curve for both electrodes showed a linear region from 0.04 to 0.11 µmol L-1 of MnTM-2-PyP5+. The limit of detection (LD) and the limit of quantification (LQ) were 19 nmol L-1 and 64 nmol L-1 for GCE, and 1.6 nmol L-1 and 5.4 nmol L-1 for CNTCPE, respectively. The method developed presented acceptable accuracy, with percentages of apparent recovery from 110% to 117% in MnP-spiked yeast biomass sample grown in the absence of MnTM-2-PyP5+. Concentrations of MnTM-2-PyP5+ from 0.08 to 0.12 µmol mg-1 were found in yeast biomass sample grown for 72 hours in YMA medium containing 20 µmol L-1 of MnTM-2-PyP5+.